If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(12 + -1x) + -11(4x + -5) = 9(-5x) + -26 (12 * 5 + -1x * 5) + -11(4x + -5) = 9(-5x) + -26 (60 + -5x) + -11(4x + -5) = 9(-5x) + -26 Reorder the terms: 60 + -5x + -11(-5 + 4x) = 9(-5x) + -26 60 + -5x + (-5 * -11 + 4x * -11) = 9(-5x) + -26 60 + -5x + (55 + -44x) = 9(-5x) + -26 Reorder the terms: 60 + 55 + -5x + -44x = 9(-5x) + -26 Combine like terms: 60 + 55 = 115 115 + -5x + -44x = 9(-5x) + -26 Combine like terms: -5x + -44x = -49x 115 + -49x = 9(-5x) + -26 Remove parenthesis around (-5x) 115 + -49x = 9 * -5x + -26 Multiply 9 * -5 115 + -49x = -45x + -26 Reorder the terms: 115 + -49x = -26 + -45x Solving 115 + -49x = -26 + -45x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45x' to each side of the equation. 115 + -49x + 45x = -26 + -45x + 45x Combine like terms: -49x + 45x = -4x 115 + -4x = -26 + -45x + 45x Combine like terms: -45x + 45x = 0 115 + -4x = -26 + 0 115 + -4x = -26 Add '-115' to each side of the equation. 115 + -115 + -4x = -26 + -115 Combine like terms: 115 + -115 = 0 0 + -4x = -26 + -115 -4x = -26 + -115 Combine like terms: -26 + -115 = -141 -4x = -141 Divide each side by '-4'. x = 35.25 Simplifying x = 35.25
| 3+8(st+3w)+3st= | | 16=3-7k-1 | | 15p+19q+p-3q-6p= | | 3x-2x+7=15 | | 12-4p=-4-6p | | 4cos^2x+4sin-1=0 | | 6.2(a+b)+2.6(a+b)+3a= | | 8t^2+3t+24=0 | | t/3-4=9 | | 8m=-12+5m | | 3x+2y+4(3x+y)= | | 2+(x+3)= | | 11*y=-22 | | 4x+3x+28=2 | | -9+5=-22 | | 6(x+2)+3(3x+7)=4(5+4x)-7 | | 7+3(uv-6)+u= | | r-8=9 | | C^2-14c+49=0 | | 50=d-0.5d | | 21-14x=29+12x | | y=7/3(-3)+5 | | 4(2x+y)+5x= | | 20-5(p+1)+3p=(2p-15) | | -x+(-2x)= | | 8(4-3x)+7(x-3)+3(9+7x)=10 | | 8=5-1/6x | | 8q+5r-7q-6r= | | 4z=13-21 | | 100-y^2=0 | | x+4x=14.95 | | x+4x=14.995 |